A descriptive study on the treatment of pediatric CRPS in the Nordic countries and Germany - Johanna Broman; Cathrin Weigel; Ludwig Hellmundt; Anna Persson (Wiley, 2021)
Abstract Pediatric complex regional pain syndrome (pCRPS) is a rare, painful state that often occurs as a complication following physical trauma. Diagnosis and treatment require specialist expertise in a multidisciplinary setting. Treatment is focused on pain reduction and improvement in function, which differs from the treatment of adult CRPS. We performed a cross‐sectional survey with the aim of identifying pain centers in the Nordic countries and Germany that specialized in treating children with pain, especially pCRPS, and sought to describe their treatment strategies. Centers and health‐care professionals working with children experiencing chronic pain were identified using internet search engines, phones, or e‐mail. A standardized set of questions and an electronic questionnaire were answered by the participants. A total of 28 participants were identified in 24 centers, which were involved with patients having pCRPS (Germany: 7, Norway: 7, Sweden: 5, Finland: 5, Denmark: 3, and Island: 1). One center in Germany treated more than 20 patients per year. Half of the identified centers (n = 12) treated between 1 and 5 children with pCRPS per year. Guidelines for treating pCRPS were reportedly followed by 9/28 responders (32%), and physiotherapy was reported to be part of the treatment routine in most centers (74%). Interventional anesthesia was rarely used. Psychological therapy: 57% answered that it was always offered, 30% replied that it was proffered in most cases, and 13% responded that it was recommended in only a few patients. Pharmacological treatments were not commonly used. Treatment resources for pCRPS are scarce in the Nordic countries and Germany. Most centers treated very few children with pCRPS and did not have established guidelines. A multidisciplinary approach was used by many centers, most often combining physiotherapy and psychotherapy, and less commonly pharmacological treatment. The difficulties in diagnosing pCRPS and finding official referral units are unfortunate, considering the potentially favorable outcome with adequate treatment.